2015
DOI: 10.3389/fpsyt.2015.00126
|View full text |Cite
|
Sign up to set email alerts
|

Attention Deficit Hyperactivity Disorder in the Light of the Epigenetic Paradigm

Abstract: Attention deficit hyperactivity disorder (ADHD) is a highly prevalent neurodevelopmental disorder characterized by a definite behavioral pattern that might lead to performance problems in the social, educational, or work environments. In the Diagnostic and Statistical Manual of Mental Disorders, Fifth Edition, the symptoms of ADHD were restricted to those associated with cognitive (attention deficit) and behavioral (hyperactivity/impulsivity) deficits, while deficient emotional self-regulation, a relevant sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 80 publications
0
33
0
4
Order By: Relevance
“…high fat/sugar) is of particular interest as it has been reported to associate with both CP and ADHD (Howard et al., ; Jacka et al., ; Liu, Raine, Venables, & Mednick, ; Sonuga‐Barke et al., ). A potential mechanism that might help explain the link between ‘unhealthy diet’ and CP and ADHD is the epigenetic process of DNA methylation, which is highly responsive to the nutritional environment (Drake et al., ), and also associates with CP‐related phenotypes (Cecil et al., ) and ADHD (Schuch, Utsumi, Costa, Kulikowski, & Muszkat, ; van Mil et al., ; Walton et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…high fat/sugar) is of particular interest as it has been reported to associate with both CP and ADHD (Howard et al., ; Jacka et al., ; Liu, Raine, Venables, & Mednick, ; Sonuga‐Barke et al., ). A potential mechanism that might help explain the link between ‘unhealthy diet’ and CP and ADHD is the epigenetic process of DNA methylation, which is highly responsive to the nutritional environment (Drake et al., ), and also associates with CP‐related phenotypes (Cecil et al., ) and ADHD (Schuch, Utsumi, Costa, Kulikowski, & Muszkat, ; van Mil et al., ; Walton et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…DNA methylation is hypothesized to link the gestational environment with adult disease (12) via persistent changes in gene expression. In autism, schizophrenia, and ADHD, aberrant DNA methylation and methyltransferase function have been implicated in development of these diseases and cognitive dysfunction (1315). In our mouse model, we have shown that offspring who were exposed to maternal HFD have whole‐genome DNA hypomethylation in multiple brain regions, including the prefrontal cortex (PFC), along with promoter‐specific hypomethylation and dysregulated gene expression (9).…”
mentioning
confidence: 99%
“…Recently, IGF2 DNA methylation may be as predisposing factor to develop ADHD (33, 54, 55). In fact, prenatal exposure to high-fat and -sugar diet promotes IGF2 DNA methylation at birth that, in turn, has been positively associated with higher ADHD symptoms (28).…”
Section: Attention-deficit/hyperactivity Disordermentioning
confidence: 99%
“…High expression of BDNF is also found in a model of autism [valproic acid (VPA)-treated rat offspring] (54). In addition to the high BDNF expression in hippocampus, the VPA-treated rats show low expression of p-Akt, Bcl-2, p-CaMKII, as well as a significant increase in Bax and caspase-3 expression (33).…”
Section: Autism Spectrum Disordermentioning
confidence: 99%